Game theoretic research on strategies for medical carbon neutrality stakeholders under time delay effects - Xie, Bo; Gao, Xuyang; Cheng, Yingying; Niu, Muqing; Liu, Shijia (Frontiers in Public Health, 2025)
IntroductionCarbon emissions from the healthcare sector have drawn increasing attention as global climate change intensifies. Achieving carbon neutrality in healthcare is vital for sustainable development, yet the complexity of stakeholder interactions and regulatory mechanisms creates substantial challenges.MethodsThis study develops a dynamic evolutionary game model with time-delay effects to examine the strategic behaviors of four stakeholders: government, public hospitals, pharmaceutical enterprises, and the public. Stability analysis is applied to determine equilibrium strategies, while MATLAB simulations explore the impacts of regulatory, financial, and reputational parameters on system dynamics.ResultsThe findings reveal that government regulation is constrained by high costs and limited credibility, indicating the need to reduce costs and enhance credibility through market-based carbon trading and information-driven supervision. Public hospitals' weak compliance, driven by short-term profit motives, can be improved by strengthening financial incentives and penalties. Pharmaceutical enterprises' self-discipline is promoted by raising fines, reinforcing reputational incentives, and expanding public oversight channels. Public participation exerts a significant influence on carbon neutrality outcomes, and optimized online engagement mechanisms coupled with flexible compensation ratios are found to enhance effectiveness. Time delays accelerate system convergence but do not alter the evolutionary direction.DiscussionThese results underscore the critical role of multi-stakeholder interaction in advancing healthcare carbon neutrality. The study provides both theoretical insights and practical policy implications for designing more effective carbon neutrality strategies in the healthcare sector.